New Diplotrema and Lavellodrilus earthworm species from southern Mexico (Annelida, Crassiclitellata, Acanthodrilidae) - Fragoso, Carlos; Rojas, Patricia (Zootaxa, 2018)
Two acanthodriline new species from the states of Tabasco and Chiapas in southern Mexico are described, Diplotrema chajulensis sp. nov. and Lavellodrilus sheylae sp.nov. Diplotrema chajulensis sp. nov. has spermathecae where the ampulla inserts at a right angle from the duct and the diverticulum continues the main axis; it is distinguished from other neotropical Diplotrema species that share this character by the pattern of genital marks and the type of penial setae. Lavellodrilus sheylae sp. nov. is unique in the genus Lavellodrilus by the unpaired condition of the mesial spermathecae; variation in the number of spermathecal diverticula (one or two) was considered a polymorphism. Finally we discuss reasons to maintain one of the new species in an austral genus (Diplotrema) in spite of some morphological differences observed among the Mexican-Cuban-Central American (MX-CA) worms and the austral species. A short esophagus in all the holoic and meroic acanthodriline earthworms from MX-CA and a mid-ventral position of spermathecal pores in Lavellodrilus are interpreted as ancestral characters that evolved and were fixed in the worms that inhabited an ancient Laurasian block, probably in response to the semi-aquatic conditions that prevailed in this region during millions of years.